Acting out: Severina as Baroness Castelli - Čale Feldman, Lada (Array, 2008)
The article discusses the controversial role the singer Severina played in the scandal surrounding the performance of Miroslav Krleža's "Honorable Glembays", directed by Branko Brezovec in spring 2007.